The impact of services that offer individualised funds, shared management, person-centred relationships, and self-direction on the lived experiences of consumers with mental illness - Peterson, Sunila; Buchanan, Angus; Falkmer, Torbjorn (BioMed Central Ltd, 2014)
BackgroundMental health service providers across Australia, including Western Australia (WA), have begun to offer individualised funds, shared management, person-centred and self-directed (SPS) services. No research exists on the impact of SPS services on the lived experiences of these particular consumers. This study explored the impact of a SPS service offered for the first time in WA to consumers with mental illness. MethodsData on sixteen consumers' lived experiences were analysed using an abbreviated grounded theory approach. These data developed by the consumers, Guides (staff) and an independent evaluator had been collected in the past prior to the commencement of the study. ResultsThree over-arching categories, and related subcategories, emerged indicating that 1) access to individualised funds enabled practical and psychological benefits to consumers; 2) consistent contact in shared management and person-centred relationships enhanced the provision of timely and meaningful staff support to consumers; and 3) high quality shared management and person-centred relationships with staff and the opportunity to self-direct enabled consumers' change and growth. ConclusionsSPS services enhanced consumers' lived experiences and enabled staff to provide and consumers to experience timely access to recovery resources, consistent contact, and responsive and high quality support, and self-direction of services. In this, consumers changed, grew and achieved desired recovery experiences. The overall impact of the SPS service seemed to be founded on the goodness of fit between person characteristics of staff and consumers, which enabled rich support that provided for corrective emotional experiences. This enabled them to build meaningful and hopeful lives where they started to live with, and beyond, their mental illness.